(untitled) (Semiárida, 2020)
The perennial forage most commonly used as complement of grasslands in La Pampa is weeping lovegrass. This work studied the initial solubility (IS) and the effective degradability (ED) of weeping lovegrass forage along the whole cycle. Five cuts were done on the following dates: November 16th, January 14th, March4th, May 15th and July 1st. The forage was divided in two fractions, sheath and stem, and incubated in the rumen of 3 fistulated Hereford steers, in nylon bags, for 3, 6, 9, 12, 24, 48, 72 and 96 hours. The IS was estimated by submerging the samples in distilled water at 39°C for 15 minutes, under constant movement. The ED of dry matter was estimated by summing up the partial disappearances, at prefixed outflow rate. The results were subjected to analysis of variance and Tukey (p < 0.05). The values of IS were similar, for the sheath fraction, in cuts 1 and 2, and clearly lower (p<0,05) from cut 3 onwards. The IS of the stem fraction showed low values from the first cut. The ED of the sheath fraction was almost 35% in cuts 1 and 2, and higher than the ED of cuts 4 and 5 (p< 0.05). The stem’s ED was low in all cuts, with no differences between them. It is concluded that the strategy of utilization of this species should be directed to obtain the highest possible sheath proportion. This study confirms that the nutritive value of weeping lovegrass is low, both as green and deferred forage.